An Empirical Study of E-Business Success Factors - Alok Chandra , Mukesh Agarwal, Parag Kalkar, Raji Rajan, Prakash Chandra Swain, (European Economic Letters (EEL), 2023)
As e-business transforms the global market, digital enterprises must comprehend its success elements. This empirical study examines e-business venture success determinants. SEO, social media, and content marketing boost website traffic and brand awareness. Customer relationship management (CRM) tactics including personalized interactions, fast customer service, and loyalty programs help develop strong customer relationships and improve customer satisfaction. Supply chain management is crucial for inventory management, delivery, and order fulfillment. Due to the rise of mobile devices, responsive design and mobile apps are essential for a good user experience, according to the report. Data analytics and insights help e-businesses make data-driven decisions, understand client behavior, and spot market trends. The survey concludes that e-businesses must innovate to keep up with technology and client expectations. This study provides actual information on e-business success factors, helping digital enterprises succeed. The findings help practitioners and decision-makers create successful strategies, allocate resources wisely, and improve their e-business competitiveness. The aim of this research paper to reveal a set of critical success factors that significantly impact the performance of e-businesses.